Media Development of “Kebun Phytagoras” for Learning Pythagoras Theorem - Lailin Hijriani; Abd. Qohar (International Journal of Trends in Mathematics Education Research, 2020)
The aim of this development research is to develop “Kebun Pythagoras” media which can be used in learning to help student to prove the truth of the Pythagorean Theorem. The development model used is the Plomp development model (2010). The development of “Kebun Pythagoras” media goes through three steps: initial research, development step, and assessment step. The results of evaluation data are suggestuins and research trial subjects’ assessments used as an input for developing the media. The results of data analysis obtained an overall average value of criteria 3.6 of 4.0 scale included valid category. The practicality result of media utilization with an overall average value of criteria 3.5 of 4.0 scale included practical category.